2010
DOI: 10.1099/vir.0.022699-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bracovirus particle proteins and analysis of their transcript levels at the stage of virion formation

Abstract: Polydnaviruses (PDVs) are unique symbiotic viruses associated with parasitic wasps; they replicate only in the calyx cells of a wasp's ovaries and are transferred at oviposition along with the parasitoid egg into the lepidopteran host. The DNA packaged in the viral particles encodes factors that manipulate the host's immune defences and development to benefit the parasitoid. PDVs are found in two subfamilies of ichneumonids (ichnoviruses) and in braconids of the microgastroid complex (bracoviruses). We recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…Analyses of these regions in Glyptapanteles and Cotesia spp. revealed that the odv-e66-like1 nudiviral gene encoding a bracovirus particle component [8] was localized between PL1 and PL2 within the macrolocus (figures 1 and 2). For C. congregata, this region was obtained by sequencing overlapping fragments isolated by PCR with primers designed based on conserved Glyptapanteles and C. sesamiae genes (figure 2 and table 1; electronic supplementary material, S5).…”
Section: Results (A) Global Proviral Segment Organization Is Conservedmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of these regions in Glyptapanteles and Cotesia spp. revealed that the odv-e66-like1 nudiviral gene encoding a bracovirus particle component [8] was localized between PL1 and PL2 within the macrolocus (figures 1 and 2). For C. congregata, this region was obtained by sequencing overlapping fragments isolated by PCR with primers designed based on conserved Glyptapanteles and C. sesamiae genes (figure 2 and table 1; electronic supplementary material, S5).…”
Section: Results (A) Global Proviral Segment Organization Is Conservedmentioning
confidence: 99%
“…This EVE corresponds to the major remnant of the nudivirus genome captured by the wasp ancestor [4,6,7], whereas other nudiviral genes have been dispersed in the wasp genome. Nudiviral genes encode the viral RNA polymerase, BV particle structural components and envelope proteins [6,8,9]. However, they are not packaged in BV particles, which instead contain multiple dsDNA circular molecules, called 'circles'.…”
Section: Introductionmentioning
confidence: 99%
“…The region is characterized by high gene density and contains intronless genes. This cluster encodes VP39 and 38K, the most abundant proteins in CiBV particles [28] and is amplified during CcBV virus particle production [36]. Other nudiviral genes are now dispersed in the C. congregata genome [10].…”
Section: (B) Bracoviruses Originate From An Ancestral Nudivirus (I) Nmentioning
confidence: 99%
“…A series of 29 nudivirus genes (nudiviruses are large dsDNA insect viruses related to baculoviruses) were expressed in the ovaries (table 1). Furthermore, one-third of these genes encoded BV particle components [10,27,28]. Last, 18 of these nudiviral genes, corresponding to baculovirus core genes [29], should perform essential functions of the virus cycle, based on functional characterization in baculoviruses [30] (table 1).…”
Section: (B) Bracoviruses Originate From An Ancestral Nudivirus (I) Nmentioning
confidence: 99%
“…Parasitoid wasps have domesticated these viruses for transferring virulence genes (21)(22)(23), interfering with the immune response and development of their lepidopteran hosts (24,25). The longdebated genuine viral nature of bracoviruses has recently been demonstrated with the discovery in wasp genomes of genes involved in bracovirus particle production (26)(27)(28). These genes, related to nudivirus and baculovirus core genes (27), establish a bridge between the phylogeny of free dsDNA viruses and geologic animal fossil data, thus allowing the exploration of deep evolutionary timescales.…”
mentioning
confidence: 99%